Electrochemotherapy combined with immunotherapy – a promising potential in the treatment of cancer - Hadzialjevic, Benjamin; Omerzel, Masa; Trotovsek, Blaz; Cemazar, Maja; Jesenko, Tanja; Sersa, Gregor; Djokic, Mihajlo (Frontiers in Immunology, 2024)
Electrochemotherapy is a novel, locoregional therapy that is used to treat cutaneous and deep-seated tumors. The electric pulses used in electrochemotherapy increase the permeability of the cell membranes of the target lesion and thus enhance the delivery of low-permeant cytotoxic drugs to the cells, leading to their death. It has also been postulated that electrochemotherapy acts as an in situ vaccination by inducing immunogenic cell death. This in turn leads to an enhanced systemic antitumor response, which could be further exploited by immunotherapy. However, only a few clinical studies have investigated the role of combined treatment in patients with melanoma, breast cancer, hepatocellular carcinoma, and cutaneous squamous cell carcinoma. In this review, we therefore aim to2 review the published preclinical evidence on combined treatment and to review clinical studies that have investigated the combined role of electrochemotherapy and immunotherapy.